2023
DOI: 10.1038/s41598-023-41057-w
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical fingerprint and biological activity of raw and heat-treated Ornithogalum umbellatum

Aytül Uzun Akgeyik,
Emine Yalçın,
Kültiğin Çavuşoğlu

Abstract: The plants that we use as food in our daily diet and as risk preventers against many diseases have many biological and pharmacological activities. The heat treatments applied during the cooking of the plants cause changes in the phytochemical content and bioactivity. In this study, the phytochemical fingerprint and biological activities of raw and heat-treated extracts of Ornithogalum umbellatum L., which is widely consumed in the Black Sea region, were investigated. The bulb and leaf parts of the plant consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In addition to its protective effects against metabolic syndrome, it also exhibits procognitive, neuroprotective, antibacterial, anticancer, anti-osteoporotic, anti-aging, and analgesic properties. Furthermore, PCA supports healthy liver, kidney, and reproductive function [5,[17][18][19].…”
Section: Characteristics and Sources Of Pcamentioning
confidence: 74%
See 2 more Smart Citations
“…In addition to its protective effects against metabolic syndrome, it also exhibits procognitive, neuroprotective, antibacterial, anticancer, anti-osteoporotic, anti-aging, and analgesic properties. Furthermore, PCA supports healthy liver, kidney, and reproductive function [5,[17][18][19].…”
Section: Characteristics and Sources Of Pcamentioning
confidence: 74%
“…However, it was found that the steam blanching method was the most effective in preserving PCA to a greater extent, confirming that this compound shows higher concentrations in raw extracts compared to those subjected to heat [43]. Indeed, it is reported that the amount of protocatechuic acid (PCA) decreases dramatically when subjected to thermal treatments, reaching up to 90% loss after boiling at 100 • C [5,44].…”
Section: Characteristics and Sources Of Pcamentioning
confidence: 96%
See 1 more Smart Citation
“…After incubation, the extract was filtered to remove all remaining solids. The filtrate was then centrifuged at 10,000 rpm for 10 min, the liquid phase was evaporated, and the pellet was used as Z. officinale extract (Akgeyik et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Group I was accepted as a negative control, and the bulbs were germinated with distilled water. In group II, which was determined as a positive control, the bulbs were treated with 25 mg/mL sodium azide (NaN 3 ), which is a potent mutagen (Akgeyik et al 2023 ). To determine whether the control and 6% FMD-treated samples were mutagenic alone, groups III and IV were germinated with 2 mg/mL control and 2 mg/mL extract from the 6% FMD group, respectively.…”
Section: Determination Of Formaldehyde Levelsmentioning
confidence: 99%